Urosepsis Causing Gastric Ischemia: A Rare but Deadly Complication - Vijay Jarodiya; Chirag Kher; Sangeetha Nanthabalan; Gunjan Shah (Case Reports in Gastrointestinal Medicine)
A 70-year-old male presented with abdominal pain and altered mental status. He was found to have sepsis secondary to a urinary tract infection with imaging showing hepatic portal venous gas and gastric pneumatosis. Esophagogastroduodenoscopy revealed gastric ischemia extending to the midbody with necrosis and biopsies confirming ischemia. The patient was treated conservatively with intermittent nasogastric tube suctioning, acid suppression therapy and broad-spectrum antibiotics. The patient improved clinically and repeat imaging and EGD showed resolution of the ischemia. The patient’s diet was advanced and he was discharged to a long-term acute care facility. Gastric ischemia is a rare condition caused by local or diffuse vascular insufficiency. Management is either surgical or conservative with acid suppression, nasogastric tube suctioning and broad-spectrum antibiotics. Gastric ischemia is often diagnosed late and can have complications such as gastric perforation which carries high morbidity and mortality.